2008
DOI: 10.2215/cjn.01330308
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Is Less Aggressive in Hemodialysis Patients than in Nonuremic Patients

Abstract: Background and objectives: The severity of liver disease among hepatitis C patients on hemodialysis is controversial. The aim of this study was to compare the clinical, biochemical, and liver histologic characteristics of hepatitis C virus (HCV) in hemodialysis patients and in those with normal renal function.Design, setting, participants, & measurements: A case-control study was carried out with 36 HCV patients on hemodialysis and 37 HCV patients with normal renal function matched for gender, age at infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 29 publications
(41 reference statements)
2
38
0
Order By: Relevance
“…As in other studies, HCV/ESRD had lower ALT levels. Review of liver biopsy specimens by a blinded pathologist demonstrated significantly increased fibrosis and inflammation in patients with normal renal function (p=0.025 and 0.003, respectively) [9]. Similar results have been previously demonstrated [39].…”
Section: Natural History Of Hcv In Esrdsupporting
confidence: 84%
See 2 more Smart Citations
“…As in other studies, HCV/ESRD had lower ALT levels. Review of liver biopsy specimens by a blinded pathologist demonstrated significantly increased fibrosis and inflammation in patients with normal renal function (p=0.025 and 0.003, respectively) [9]. Similar results have been previously demonstrated [39].…”
Section: Natural History Of Hcv In Esrdsupporting
confidence: 84%
“…As mentioned, HCV/ESRD patients may have near normal ALT levels and low HCV viral loads [38]. Trevizoli [9] compared biochemical parameters and liver biopsies in 73 HCV patients with normal renal function and ESRD during a mean follow-up of about 12 years. As in other studies, HCV/ESRD had lower ALT levels.…”
Section: Natural History Of Hcv In Esrdmentioning
confidence: 99%
See 1 more Smart Citation
“…Although patients on dialysis tend to have milder liver disease and normal liver enzymes compared with patients with normal renal function [70] , patients with end-stage renal disease (ESRD) and CHC might have severe chronic hepatitis on liver biopsy [71] . A liver biopsy should be performed in patients with CHC who are receiving hemodialysis [72] and do not have major comorbidities.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…On the other hand, chronic dialysis patients often presented with occult viral hepatitis with less prominent clinical manifestations (14,15), as well as lower serum aminotransferase activity (16). Moreover, ESRD with HCV infection also has been suggested to have a less progressive course of liver disease (17). Does this unique response to hepatitis modify the survival of ESRD patients developing HCC?…”
Section: Introductionmentioning
confidence: 99%